Microtopographical patterns promote different responses in fibroblasts and Schwann cells: A possible feature for neural implants. Issue 1 (29th June 2020) - Mobini, Sahba; Kuliasha, Cary A.; Siders, Zachary A.; Bohmann, Nicole A.; Jamal, Syed‐Mustafa; Judy, Jack W.; Schmidt, Christine E.; Brennan, Anthony B.
Abstract: The chronic reliability of bioelectronic neural interfaces has been challenged by foreign body reactions (FBRs) resulting in fibrotic encapsulation and poor integration with neural tissue. Engineered microtopographies could alleviate these challenges by manipulating cellular responses to the implanted device. Parallel microchannels have been shown to modulate neuronal cell alignment and axonal growth, and Sharklet™ microtopographies of targeted feature sizes can modulate bio‐adhesion of an array of bacteria, marine organisms, and epithelial cells due to their unique geometry. We hypothesized that a Sharklet™ micropattern could be identified that inhibited fibroblasts partially responsible for FBR while promoting Schwann cell proliferation and alignment. in vitro cell assays were used to screen the effect of Sharklet™ and channel micropatterns of varying dimensions from 2 to 20 μm on fibroblast and Schwann cell metrics (e.g., morphology/alignment, nuclei count, metabolic activity), and a hierarchical analysis of variance was used to compare treatments. In general, Schwann cells were found to be more metabolically active and aligned than fibroblasts when compared between the same pattern. 20 μm wide channels spaced 2 μm apart were found to promote Schwann cell attachment and alignment while simultaneously inhibiting fibroblasts and warrant further in vivo study on neural interface devices. No statistically significant trends between cellular responses and geometrical parameters were identified because mammalian cells can change their morphology dependent on their environment in a manner dissimilar to bacteria. Our results showed although surface patterning is a strong physical tool for modulating cell behavior, responses to micropatterns are highly dependent on the cell type.